Adiposity and Blood Pressure in 110 000 Mexican Adults. Issue 4 (April 2017) - Gnatiuc, Louisa; Alegre-Díaz, Jesus; Halsey, Jim; Herrington, William G.; López-Cervantes, Malaquías; Lewington, Sarah; Collins, Rory; Tapia-Conyer, Roberto; Peto, Richard; Emberson, Jonathan R.; Kuri-Morales, Pablo
Abstract : Previous studies have reached differing conclusions about the importance of general versus central markers of adiposity to blood pressure, leading to suggestions that population-specific adiposity thresholds may be needed. We examined the relevance of adiposity to blood pressure among 111 911 men and women who, when recruited into the Mexico City Prospective Study, were aged 35 to 89 years, had no chronic disease, and were not taking antihypertensives. Linear regression was used to estimate the effects on systolic and diastolic blood pressure of 2 markers of general adiposity (body mass index and height-adjusted weight) and 4 markers of central adiposity (waist circumference, hip circumference, waist:hip ratio, and waist:height ratio), adjusted for relevant confounders. Mean (SD) adiposity levels were: body mass index (28.7±4.5 kg/m 2 ), height-adjusted weight (70.2±11.2 kg), waist circumference (93.3±10.6 cm), hip circumference (104.0±9.0 cm), waist:hip ratio (0.90±0.06), and waist:height ratio (0.60±0.07). Associations with blood pressure were linear with no threshold levels below which lower general or central adiposity was not associated with lower blood pressure. On average, each 1 SD higher measured adiposity marker was associated with a 3 mm Hg higher systolic blood pressure and 2 mm Hg higher diastolic blood pressure (SEs <0.1 mm Hg), but for the waist:hip ratio, associations were only approximately half as strong. General adiposity associations were independent of central adiposity, but central adiposity associations were substantially reduced by adjustment for general adiposity. Findings were similar for men and women. In Mexican adults, often overweight or obese, markers of general adiposity were stronger independent predictors of blood pressure than measured markers of central adiposity, with no threshold effects. Abstract : Supplemental Digital Content is available in the text.